Pyrazinamide Resistance, Mycobacterium tuberculosis Lineage and Treatment Outcomes in San Francisco, California - Budzik, Jonathan M.; Jarlsberg, Leah G.; Higashi, Julie; Grinsdale, Jennifer; Hopewell, Phil C.; Kato-Maeda, Midori; Nahid, Payam (PloS one, 2014)
Pyrazinamide (PZA) is a first line agent for the treatment of active tuberculosis. PZA is also considered a potent companion drug for newer regimens under development. There are limited data on the demographic, clinical, and pathogen characteristics of PZA resistant tuberculosis. Using a retrospective cohort study design, we evaluated all PZA resistant M. tuberculosis (M.tb) and M. bovis cases reported in San Francisco from 1991 to 2011. Demographic, clinical, and molecular data were analyzed. M.tb lineage was determined for all PZA resistant strains and compared to PZA susceptible strains. PZA resistance was identified in 1.8% (50 of 2,842) of mycobacterial isolates tested, corresponding to a case rate of 0.3 per 100,000 in the population. Monoresistant PZA infection was associated with the Hispanic population ([OR], 6.3; 95% [CI], 1.97-20.16) and 48% of cases were due to M. bovis. Infection with monoresistant PZA was also associated with extrapulmonary disease ([OR], 6.0; 95% [CI], 2.70-13.26). There was no statistically significant difference between treatment failure and mortality rates in patients infected with PZA monoresistance compared to pansusceptible controls (4% vs. 8%, p = 0.51), or those with PZA and MDR resistance (PZA-MDR) compared to MDR controls (18% vs. 29%, p = 0.40). PZA resistance was not associated with M.tb lineage. Across two decades of comprehensive epidemiologic data on tuberculosis in San Francisco County, PZA resistance was uncommon. PZA resistance caused predominantly extrapulmonary disease and was more common in Hispanics compared to other ethnicities, with nearly half the cases attributed to M. bovis. No association was found between PZA monoresistance and M.tb lineage. Treatment outcomes were not adversely influenced by the presence of PZA resistance.